A Combined Photochemical and Multicomponent Reaction Approach to Precision Oligomers. Issue 14 (5th February 2018) - Konrad, Waldemar; Bloesser, Fabian R.; Wetzel, Katharina S.; Boukis, Andreas C.; Meier, Michael A. R.; Barner‐Kowollik, Christopher
Abstract: We introduce the convergent synthesis of linear monodisperse sequence‐defined oligomers through a unique approach, combining the Passerini three‐component reaction (P‐3CR) and a Diels–Alder (DA) reaction based on photocaged dienes. A set of oligomers is prepared resting on a Passerini linker unit carrying an isocyano group for chain extension by P‐3CR and a maleimide moiety for photoenol conjugation enabling a modular approach for chain growth. Monodisperse oligomers are accessible in a stepwise fashion by switching between both reaction types. Employing sebacic acid as a core unit allows the synthesis of a library of symmetric sequence‐defined oligomers. The oligomers consist of alternating P‐3CR and photoblocks with molecular weights up to 3532.16 g mol −1, demonstrating the successful switching from P‐3CR to photoenol conjugation. In‐depth characterization was carried out including size‐exclusion chromatography (SEC), high‐resolution electrospray ionization mass spectrometry (ESI‐MS) and NMR spectroscopy, evidencing the monodisperse nature of the precision oligomers. Abstract : Sequence control : The synthesis of multifunctional precision sequence‐defined linear macromolecules becomes possible by fusing a highly efficient photochemical and multicomponent reaction approach entailing alternating Passerini and photoblocks. The growth of the oligomers is based on a convergent chain extension concept of sebacic acid with building blocks on demand in an orthogonal fashion (see figure).